THE REJUVENATION OF AKHLAK EDUCATION IN ISLAMIC EDUCATION - Ridholloh, Ridholloh; Syarif, Fajar (Ibn Khaldun University, Bogor, 2022)
This paper is a literature study on akhlak education contained in Islamic education. The discussion focused on the role of religion on akhlaks. Akhlak education really requires the role of religion that has urgency and significance in akhlaks. Therefore, it is necessary to rejuvenate the akhlak education contained in Islamic education, so that akhlak education becomes attractive. This paper finds that akhlak education contained in Islamic education is constructed based on religious relations. Therefore, akhlak education strengthens Islamic education.